Extremely Rare Case of Vulvar Myxoid Epithelioid Sarcoma - Joana Lima Rego; Georgia Fontes Cintra; Ana Karina Junqueira Netto; Lucas Faria Abrahão-Machado; Audrey Tsunoda (Case Reports in Obstetrics and Gynecology)
Epithelioid sarcoma is a distinct sarcoma type with specific morphology and immunophenotype. An epithelioid sarcoma of the vulva is an extremely rare and aggressive tumor and most commonly occurs on the labia majora in women of reproductive age. Only few cases have been reported, especially with the presence of focal myxoid changes. Early diagnosis is difficult because of its benign appearance as a painless subcutaneous nodule. Optimal treatment is not well established due to its rarity. We report a successfully approached case of vulvar epithelioid sarcoma that occurred in a 34-year-old female patient, treated with wide local excision, and review of the current medical literature.